Edukasi ekowisata berbasis pelibatan masyarakat di Danau Lubuk Siam - Muhammad Fauzi; Andri Hendrizal; Yudho Harjoyudanto; Eko Prianto; Bintal Amin (Unri Conference Series: Community Engagement, 2022)
Seasonal floods in Lake Lubuk Siam are already rare. This flood brought a lot of nutrients and fish into Lake Lubuk Siam. This results in a lack of fishermen's catches, so finding alternative sources of additional income for the surrounding community is necessary. This service uses the Participatory Rural Appraisal (PRA) method, which seeks to actively involve the community in efforts to develop an ecotourism area in Lake Lubuk Siam. The educational activity on ecotourism development in Lake Lubuk Siam was attended by 30 people consisting of the village government, the chairman, and members of the fishermen's group. Based on the questionnaire results, it can be seen that many people still did not understand the concept of ecotourism. Some others even consider that there is no potential for ecotourism development in their area. However, after socialization and education, the community understood and realized that the aquatic resources in their area could be developed into an ecotourism area. Through the results of this education, it can be concluded that the local community in Lake Lubuk Siam already has sufficient information as the primary capital for developing ecotourism independently in their area.